2021
DOI: 10.1002/bse.2843
|View full text |Cite
|
Sign up to set email alerts
|

Climate change mitigation: Carbon assurance and reporting integrity

Abstract: Concern about climate change has increased the pressure on firms to be accountable for social impact and to report on environmental, social and governance (ESG) performance. Focusing on the view that sustainability-oriented firms are likely to consider wider stakeholder interests and pursue high financial reporting integrity, this paper examines the association between carbon assurance and earnings management.Using a sample of firms listed on the New York Stock Exchange, we find voluntary adoption of carbon as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 84 publications
1
29
0
Order By: Relevance
“…However, researchers disagree on whether board gender diversity creates value for firms, and empirical results are mixed (Post & Byron, 2015). For example, Bui et al (2021) find that having more female directors reduces earnings management. Adams and Ferreira (2009) suggest that having female board of directors enhances firm monitoring but is also associated with negative firm performance.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…However, researchers disagree on whether board gender diversity creates value for firms, and empirical results are mixed (Post & Byron, 2015). For example, Bui et al (2021) find that having more female directors reduces earnings management. Adams and Ferreira (2009) suggest that having female board of directors enhances firm monitoring but is also associated with negative firm performance.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…There is increasing market demand for non‐financial information reporting, particularly on the firm‐level movement toward their sustainable development goals. Nevertheless, corporate ESG disclosure is still on a voluntary basis (Bui et al, 2021) and overseen by the US Securities and Exchange Commission. As there are no framework and regulation for ESG disclosure in the United States, firms may choose to report ESG information when and where they see fit (de Villiers & van Staden, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, establishing good quality of reported carbon information is pertinent to stakeholders. In the second strand of carbon research, studies have provided empirical evidence that firms' carbon reporting tends to reflect their commitment to ecological improvement and carbon information is thus relevant in decision-making in the stock market (Bui et al, 2020(Bui et al, , 2021Luo & Tang, 2014;Matsumura et al, 2014). Specifically, some studies have reported a positive role of carbon disclosure on the stock market (Alsaifi et al, 2019) or confirmed the relationship between carbon performance and carbon disclosure (Giannarakis et al, 2017) or evidenced the use of carbon offsetting information for product decisions by consumers (Warburg et al, 2021).…”
mentioning
confidence: 99%